2017
DOI: 10.1080/17470919.2017.1285812
|View full text |Cite
|
Sign up to set email alerts
|

The role of parietal cortex in overimitation: a study with fNIRS

Abstract: Previous studies have shown right parietal activation in response to observing irrational actions. Behavioral studies show that people sometimes imitate irrational actions, a phenomenon called overimitation. However, limitations on movement in functional magnetic resonance imaging (fMRI) mean that the neural basis of overimitation has not been studied. To address this, our study employed a less restrictive neuroimaging technique, functional near-infrared spectroscopy (fNIRS). Measurements were taken while part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
3
0
2
Order By: Relevance
“…Others take advantage of the flexibility of fNIRS to examine neural response to affective touch 131 or to imitation behavior. 132 For example, in the latter paper, participants completed an interactive task in which they saw a demonstrator make typical straight actions or abnormal curved actions and then had the opportunity to imitate them; right inferior parietal cortex showed a stronger activation signal when viewing the curved actions, which replicates previous fMRI studies. However, in fMRI, it is very hard to implement the imitation actions, and fNIRS provides more flexibility to explore the neural mechanisms of interactive behavior.…”
Section: Overview Of Novel Applications Of Fnirssupporting
confidence: 71%
See 1 more Smart Citation
“…Others take advantage of the flexibility of fNIRS to examine neural response to affective touch 131 or to imitation behavior. 132 For example, in the latter paper, participants completed an interactive task in which they saw a demonstrator make typical straight actions or abnormal curved actions and then had the opportunity to imitate them; right inferior parietal cortex showed a stronger activation signal when viewing the curved actions, which replicates previous fMRI studies. However, in fMRI, it is very hard to implement the imitation actions, and fNIRS provides more flexibility to explore the neural mechanisms of interactive behavior.…”
Section: Overview Of Novel Applications Of Fnirssupporting
confidence: 71%
“… showed that both infants and mothers have a positive fNIRS response in the PFC when seeing videos of the other smiling. Others take advantage of the flexibility of fNIRS to examine neural response to affective touch or to imitation behavior . For example, in the latter paper, participants completed an interactive task in which they saw a demonstrator make typical straight actions or abnormal curved actions and then had the opportunity to imitate them; right inferior parietal cortex showed a stronger activation signal when viewing the curved actions, which replicates previous fMRI studies.…”
Section: Overview Of Novel Applications Of Fnirssupporting
confidence: 66%
“…Functional near-infrared spectroscopy (fNIRS) is a non-invasive device designed to monitor cerebral hemodynamics, a method commonly used to assess cerebral activity [34]. fNIRS is a small and portable machine that is less vulnerable to head and body motion artifacts and can measure brain activity in an environment closer to daily life.…”
Section: Introductionmentioning
confidence: 99%
“…The current study aims to test the social-signalling hypothesis of imitation in a rigorous manner, avoiding confounding factors that have affected previous studies. In this study pairs of naïve adult participants were asked to move blocks from one location to another in a specified order (Oliver, Tachtsidis, & Hamilton, 2017) (Figure 1). This augmented-reality setup provided a rich interactive context while avoiding experimenter effects.…”
Section: Introductionmentioning
confidence: 99%